Acute Bilateral Superior Branch Vestibular Neuropathy - Yacovino, Dario A.; Finlay, John B.; Urbina Jaimes, Valentina N.; Verdecchia, Daniel H.; Schubert, Michael C. (Frontiers in Neurology, 2018)
The rapid onset of a bilateral vestibular hypofunction (BVH) is often attributed to vestibular ototoxicity. However, without any prior exposure to ototoxins the idiopathic form of BVH is most common. Although sequential bilateral vestibular neuritis (VN) is described as a cause of BVH, clinical evidence for simultaneous and acute onset bilateral VN is unknown. We describe a patient with an acute onset of severe gait ataxia and oscillopsia with features compatible with acute BVH putatively due to a bilateral VN, which we serially evaluated with clinical and laboratory vestibular function testing over the course of 1 year. Initially, bilateral superior and horizontal semicircular canals and bilateral utricles were impaired, consistent with damage to both superior branches of each vestibular nerve. Hearing was spared. Only modest results were obtained following six months of vestibular rehabilitation. At a one-year follow-up, only the utricular function of one side recovered. This case is the first evidence supporting an acute presentation of bilateral VN as a cause for BVH, which would not have been observed without critical assessment of each of the 10 vestibular endorgans.